DIPG-33. HARMONIZATION AND CHARACTERIZATION OF POSTMORTEM DONATIONS FOR PEDIATRIC BRAIN TUMORS. (23rd April 2019) - Kambhampati, Madhuri; Panditharatna, Eshini; Yadavilli, Sridevi; Ho, Cheng-Ying; Almira-Suarez, Isabel; Bornhorst, Miriam; Kilburn, Lindsay; Hwang, Eugene; Rood, Brian; Georgescu, Maria-Magdalena; Rance, Naomi; Mueller, Sabine; et al.
Abstract: RATIONALE: A major factor contributing to the expanding knowledge of CNS tumors, specifically DMG biology is the selfless gift from patients and their families of postmortem tumor tissue. To facilitate this, we developed a postmortem donation program for collection of tissue and biospecimens for accelerating biology studies of end stage disease for pediatric CNS tumors. METHODS: Our postmortem program entails coordinating tissue donations, compiling clinical data, processing of whole brain, spinal cord, biofluids, and germline controls. Through our protocol, primary and disseminated tumor specimens are designated for molecular characterization and for generation of a matched preclinical model. RESULTS: During the past eight years, we coordinated and accrued over 50 autopsy cases including diffuse midline gliomas, ATRT, ETANTR, CPC from 20 institutions across North America and the United Kingdom. We report that approaching a family at the time of progression has provided the most successful outcome for consent to our program. Patient age range was from 11months to 20 years old. The median time from postmortem donation to tissue processing range was 13 hours with the earliest time point being 4 hours and the longest being 96 hours. All collected specimens were successfully processed and assessed for DNA/RNA integrity using bioanalyzer, attempted primary neurosphere cultures and cryopreserved for future molecular studies. PDX generation from fresh tissue proved more successful compared to primary neurospheres and post mortem time did not seem to have an effect. We have successfully generated models that represent molecular subgroups of DMGs such as H3.3/ H3.1- K27M and H3 WT. All generated preclinical models were validated by STR analysis and immunohistochemical assays using human mitochondrial antibodies. IMPACT: Postmortem tissue donations serve as an invaluable source for access to end-stage disease biology, generation of PDX models, studying patterns of tumor migration, testing combination therapy and preclinical drug testing.